Being a Muslim In a Catholic Family and Vice Versa: Religious Education in Mixed-Faith Families in Flores, Eastern Indonesia - Fransiska Widyawati (Ulumuna, 2022)
This study explores religious education and identity formation among families within mixed-faith families in Flores, Eastern Indonesia, specifically, Muslim-Catholic families. This ethnographic research observes and holds in-depth interviews with eight mixed-faith families comprising four to eight family members. This study finds that mixed-faith families continue to carry out the process of faith education and identity formation for all their members. However, the presence of family members with different religions gives a distinctive character because there are always negotiations, adaptations, and even transformations. The form, intensity, and model of faith education between families differ depending on the context of a mixed-faith family formation, one's position and power in the family, one's way of thinking about religion, and the spiritual environment around the family. Faith education in a mixed-faith family can positively deepen faith, strengthen religious identity, increase knowledge about other religions, foster tolerance, and appreciate diversity. This can also fade away the identity and belief of the minority and even can lead to conversion. However, the bond of family love does not cause differences, fights and conversions into one meaningful conflict.